2015
DOI: 10.1097/wco.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein and Lewy pathology in Parkinson's disease

Abstract: These recent findings open up new avenues of investigation into the molecular pathogenesis of Parkinson's disease. Future work will need to identify the most toxic conformations of α-synuclein and define their relationship to Lewy pathology. This work will be necessary to be able to develop novel therapeutic strategies that target specific pathogenic forms of α-synuclein for disease modification in Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 40 publications
0
60
0
2
Order By: Relevance
“…In the brain, α-synuclein (α-syn) exists in monomeric, oligomeric and more-aggregated forms, such as fibrils 19 . The factors governing the transition between these forms in vivo are not known, and how these forms might spread is unresolved.…”
Section: Does Lp Retrogradely Spread In Cpd?mentioning
confidence: 99%
“…In the brain, α-synuclein (α-syn) exists in monomeric, oligomeric and more-aggregated forms, such as fibrils 19 . The factors governing the transition between these forms in vivo are not known, and how these forms might spread is unresolved.…”
Section: Does Lp Retrogradely Spread In Cpd?mentioning
confidence: 99%
“…From theoretical perspective, the NAC terminus of α-Syn is a hydrophobic region, and it can bind to many moleculars and regulate their activity [6,9,44]. Here, we found that the NAC domain of α-Syn could interact with PP2A Cα and upregulate its activity.…”
Section: Discussionmentioning
confidence: 60%
“…As we know, α-Syn is a natively unfolded protein with a tendency to aggregate by the hydrophobic interaction [8,13,44]. After aggregation, the hydrophobic domain of α-Syn may be blocked, so α-Syn aggregates should less upregulate the PP2A activity than monomers.…”
Section: Blocking the Nac Domain Of α-Syn Declined Its Regulating Effmentioning
confidence: 99%
“…Current research indicates that multiple factors involved in the pathogenesis of PD, including spontaneous process of cells, namely autophagy lysosome dysfunction [3], proteasome dysfunction, mitochondrial dysfunction [4]; non-spontaneous process of cells, such as neuroinflammatory reactions, apoptosis, oxidative stress and loss of nutritional support [5,6]. There are many crossing signal system between the various molecular mechanisms [7,8].…”
mentioning
confidence: 99%
“…Initial characterization of the pathology in PD (Parkinson's disease) focused attention on the presence of the Lewy body in remaining dopaminergic neurons and the role played by melanin [1,2]. Current research indicates that multiple factors involved in the pathogenesis of PD, including spontaneous process of cells, namely autophagy lysosome dysfunction [3], proteasome dysfunction, mitochondrial dysfunction [4]; non-spontaneous process of cells, such as neuroinflammatory reactions, apoptosis, oxidative stress and loss of nutritional support [5,6].…”
mentioning
confidence: 99%